2019
DOI: 10.1111/and.13296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginger (Zingiber officinale) on semen quality

Abstract: To date, according to the Scopus database, the biological effects of ginger (binominal name: Zingiber officinale), or ginger extracts, and its derived compounds on semen quality and sperm parameters have been revealed in more than 35 original articles. Though, still, there are no collective systematic or narrative discussion and conclusion of this specific research streak. Here, we systematically review and summarise the current link between ginger and its bioactive compounds with semen quality. To achieve thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 65 publications
3
19
0
1
Order By: Relevance
“…Other mechanisms include increasing testicular weight, increasing blood flow to the testes and recycling testosterone receptors. Accordingly, the positive impact of ginger on sperm parameters, and thus on semen quality, may be attributable, at least in part, to the increased levels of gonadal hormones (testosterone and luteinising hormone; Banihani, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Other mechanisms include increasing testicular weight, increasing blood flow to the testes and recycling testosterone receptors. Accordingly, the positive impact of ginger on sperm parameters, and thus on semen quality, may be attributable, at least in part, to the increased levels of gonadal hormones (testosterone and luteinising hormone; Banihani, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, there were no statistically important differences for spermatozoa parameters (count and motility) between the study groups. Besides, no side effects were reported by patients (Hosseini et al, 2016;Gholamnezhad et al, 2018;Banihani, 2019).…”
Section: Clinical Studiesmentioning
confidence: 85%
“…Moreover, a study recruited thirty‐six subjects who used 300 mg of aspirin, for 2 months, found that the level of H 2 O 2 increased significantly after one month of use of aspirin (Bouzenna et al, ). Given that one major cause of reduced sperm function is ROS build‐up and formation of oxidative stress (Aitken, Smith, Jobling, Baker, & Iuliis, ; Banihani, , ; Bisht, Faiq, Tolahunase, & Dada, ), which disrupts the integrity of sperm DNA and damages the lipids and proteins in sperm plasma membrane (Ali Banihani & Al‐Khawalde, ; Barati, Nikzad, & Karimian, ; Wright, Milne, & Leeson, ), then, based on the above evidence, it can be suggested that aspirin affects negatively sperm function by inducing oxidative stress.…”
Section: Mechanistic Studiesmentioning
confidence: 99%